El Excentrico, 1964-07-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
July 20, 1964 [20 de Julio de 1964]. Ano 14, No 19. Cover has a advertisement of Flores Pharmacy, with pharmacists Bill Ellis and Mary Lou Flores explaining pharmaceutical standards to director Humberto Garcia. The headline reads, "Bill Ellis Pharmacist. Miss Mary Lou Flores explain pharmaceutical standards to Humberto Garcia."